Pacific Ocean Variability Influences the Time of Emergence of a Seasonally Ice‐Free Arctic Ocean. Issue 4 (15th February 2019) - Screen, J. A.; Deser, C.
Abstract: The Arctic Ocean is projected to become seasonally ice‐free before midcentury unless greenhouse gas emissions are rapidly reduced, but exactly when this could occur depends considerably on internal climate variability. Here we show that trajectories to an ice‐free Arctic are modulated by concomitant shifts in the Interdecadal Pacific Oscillation (IPO). Trajectories starting in the negative IPO phase become ice‐free 7 years sooner than those starting in the positive IPO phase. Trajectories starting in the negative IPO phase subsequently transition toward the positive IPO phase, on average, with an associated strengthening of the Aleutian Low, increased poleward energy transport, and faster sea‐ice loss. The observed IPO began to transition away from its negative phase in the past few years. If this shift continues, our results suggest increased likelihood of accelerated sea‐ice loss over the coming decades, and an increased risk of an ice‐free Arctic within the next 20–30 years. Plain Language Summary: Manmade climate change is causing a rapid loss of Arctic sea ice. Summer Arctic sea ice is predicted to disappear almost completely by the middle of this century, unless emissions of greenhouse gases are rapidly reduced. The speed of sea‐ice loss is not constant over time, however. Natural climate variability can add to the manmade decline, leading to faster sea‐ice loss, or can subtract from the manmade decline, leading to slower sea‐ice loss. In this study, we looked at how natural climate variability affects the timing of an ice‐free Arctic. We found that a natural cycle called the Interdecadal Pacific Oscillation, or IPO for short, is particularly important. Arctic sea‐ice loss is faster when the IPO is moving from its cold to warm phase and slower when the IPO is moving from its warm to cold phase. This is because variations in the IPO cause changes in atmospheric wind patterns, which alter the amount of heat that is transported into the Arctic. Observations show that the IPO started to shift from its cold to warm phase in the past few years. If this shift continues, our results suggest that there is an increased chance of accelerated sea‐ice loss over the coming decades. Key Points: Modeled trajectories to, and time of emergence of, an ice‐free Arctic are modulated by concomitant shifts in Pacific Ocean variability Faster sea‐ice loss during the shift from the negative to the positive phase of the Interdecadal Pacific Oscillation leads to earlier ice‐free Arctic There is increased likelihood of accelerated Arctic sea‐ice loss over the coming decades if current shift of Interdecadal Pacific Oscillation continues